Creating a Sufi soundscape: Recitation (dhikr) and audition (samā') according to Ahmad Kāsānī Dahbīdī (d. 1542). (1st May 2014) - Papas, Alexandre
A famous Naqshbandī Sufi, Ahmad Kāsānī Dahbīdī, surnamed Makhdūm-i A'zam, had great influence on Islamic practices and thought in the Chinese part of Central Asia as early as the late sixteenth century when his descendants, known as Makhdū-mzāda, conducted missionary campaigns in the Tarim basin. Among the 30 or so treatises that he wrote, two are of particular interest for understanding Islamic soundscapes. The first work is entitled Risāla-yi dhikr, or Treatise on Recitation, and describes the devotional repetition of the profession of faith (shahāda). The second text is devoted to the practice of spiritual audition (samā'). This Risāla-yi samā'iyya is basically a defence of Sufi musical performances. A close reading of the texts shows that the master nourished the ambition to promote a profound and encompassing vision of Sufi practices, which would educate and, at the same time, enlarge his circles of disciples. Despite the later divisions among the Makhdūmzāda branches, and the heated debates on forms of dhikr and samā', Ahmad Kāsānī's teaching was an inaugural act that has left a deep legacy for the Sufi soundscape of Xinjiang.